The potential of attached growth of microalgae on solid surface for biomass and lipid production. Issue 1 (November 2020) - Chuah, Sze Yu; Dasan, Yaleeni Kanna; Cheng, Yoke Wang; Lim, Jun Wei; Ho, Yeek Chia; Tan, Inn Shi; Yew Foo, Henry Chee; Kiew, Peck Loo; Leong, Sim Siong; Lam, Man Kee
Abstract: Microalgae cultivation is usually performed via suspended growth system; however, the subsequent harvesting technologies are either costly or energy intensive. Herein, attached growth of Chlorella vulgaris was investigated using low-cost supporting materials (polystyrene foam and cotton duct) to ease the microalgae harvesting process. Cotton duct served as a better supporting material than polystyrene foam as it promoted microalgae attachment. Evidently, the attached cultivation performed on cotton duct granted higher biomass yield (16.40 g/m 2 ) than the attached cultivation with polystyrene foam (11.70 g/m 2 ) after 14 days of cultivation. From the studied range of 0.1 – 0.3 v/v%, the optimal inoculum concentration for the attached cultivation of C. vulgaris on cotton duct was 0.3 v/v%. After 14 days of cultivation, the optimized attached cultivation of C. vulgaris was capable to produce a biomass yield of 18.2 g/m 2 . The lipid content of dried microalgae from optimized attached cultivation (43 wt%) was higher than that of suspended cultivation (32.7 wt%).